The Chicken Fallacy and the Ethics of Cruelty to Non-Human Animals - Aina, Akande Michael; Emmanuel, Ofuasia (Bangladesh Journal of Bioethics, 2017)
The ideological underpinning that guides our interaction with non-human animals needs revision. The traditional outlook, according to which humans have a higher moral status vis-à-vis non-human animals, is now otiose. If these claims are to be justified, what ideological framework would serve this end? What are the moral implications of endorsing the view that humans possess no higher moral status than non-human animals? This work takes as foundation Charles Darwins theory of evolution, which affirms that humans emerged from the long chain of evolutionary history, where non-human animals have been the carriers of the genes that shaped humans. A revisit to the discourse on the moral implication of humans cruelty to their ancestors and neighbours becomes pertinent. This essay goes against the mainstream and dominant perspective that non-human animals exist to serve human ends and as such can be treated with disdain. The thesis of this paper goes beyond Peter Singers submission that sentience is the basis for conferring moral worth on non-human animals. It affirms that in addition to sentience, good neighbourliness is a factor in determining the moral worth of non-human animals. It submits that cruelty to reared and domesticated animals may produce violent and wild species of these animals kind in a future evolution, thereby endangering the lives of future human generation, through negative alteration of genes. In the end, this paper proposes the principle of biological altruism as a suitable norm for determining the moral worth of non-human animals.